Nota sobre la historia natural de Acineta (Orchidaceae) y su abeja polinizadora, Eufriesea concava (Hymenoptera: Apidae), en Costa Rica - Cascante Marín, Alfredo (2011)
This paper reports the interaction between Acineta chrysantha (Orchidaceae) and Eufriesea concava (Apidae) in a cloud forest in the Central Valley of Costa Rica. The purpose is to encourage researchers and students to document these interactions in pollination, especially in poorly known, through the collection of specimens and deposit them into recognized biological collections. The conservation status of A. chrysantha is described